Direct Correlation between Sialic Acid Binding and Infection of Cells by Two Human Polyomaviruses (JC Virus and BK Virus) - Dugan, Aisling S. (American Society for Microbiology (ASM), 2008)
For the human polyomaviruses JC virus (JCV) and BK virus (BKV), the first step to a successful infection involves binding to sialic acid moieties located on the surfaces of host cells. By stripping and then reconstituting specific sialic acid linkages on host cells, we show that JCV uses both α(2,3)-linked and α(2,6)-linked sialic acids on N-linked glycoproteins to infect cells. For both JCV and BKV, the sialic acid linkages required for cell surface binding directly correlate with the linkages required for infection. In addition to sialic acid linkage data, these data suggest that the third sugar from the carbohydrate chain terminus is important for virus binding and infection.